Modeling for Shell-Side Heat Transfer Coefficient and Pressure Drop of Helical Baffle Heat Exchangers. Issue 2 (22nd January 2017) - Azar, Reza Tasouji; Khalilarya, Shahram; Jafarmadar, Samad; Ranjbar, Faramarz
Abstract: This study has suitably modified the existing heat transfer and pressure drop correction factors of the modified Bell–Delaware method used for heat exchangers with segmental baffles, taking into consideration the helical baffle geometry. These correction factors are presented in parametric formulas based on the Taborek presented procedure for segmental baffles. These formulas are functions of the geometrical and physical parameters of discontinuous helical baffles. In addition, the parametric formulas are presented graphically based on the Stehlik method. The correction design method proposed by Stehlik for the helical baffle is presented in detail and a theoretical model for shell-side heat transfer and pressure drop is developed. In general, the results show that the present model matches more closely with the graphically proposed correction factors of Stehlik. In order to calculate the shell-side heat transfer coefficient and pressure drop using the present method, a computational code has been developed by the authors. In addition, in order to examine the validity, the results of the code for a case study are compared with the results obtained from EXPRESS software and experimental formulas presented by Zhang. The results of comparison show that the proposed method is accurate and can be used by designers confidently.